Identification of viral infections in the prostate and evaluation of their association with cancer - Martínez Fierro, Margarita de la Luz; Leach, Robin J.; Gómez Guerra, Lauro Salvador; Garza Guajardo, Raquel; Johnson Pais, Teresa; Beuten, Joke; Morales Rodríguez, Idelma Berenise; Hernandez Ordoñez, Mario A.; Calderon Cardenas, German; Ortiz López, Rocío; Rivas Estilla, Ana María; Ancer Rodríguez, Jesús; et al. (2010)
Background: Several viruses with known oncogenic potential infect prostate tissue, among these are the polyomaviruses BKV, JCV, and SV40; human papillomaviruses (HPVs), and human cytomegalovirus (HCMV) infections. Recently, the Xenotropic Murine Leukemia Virus-related gammaretrovirus (XMRV) was identified in prostate tissue with a high prevalence observed in prostate cancer (PC) patients homozygous for the glutamine variant of the RNASEL protein (462Q/Q). Association studies with the R462Q allele and non-XMRV viruses have not been reported. We assessed associations between prostate cancer, prostate viral infections, and the RNASEL 462Q allele in Mexican cancer patients and controls. Methods: 130 subjects (55 prostate cancer cases and 75 controls) were enrolled in the study. DNA and RNA isolated from prostate tissues were screened for the presence of viral genomes. Genotyping of the RNASEL R462Q variant was performed by Taqman method. Results: R/R, R/Q, and Q/Q frequencies for R462Q were 0.62, 0.38, and 0.0 for PC cases and 0.69, 0.24, and 0.07 for controls, respectively. HPV sequences were detected in 11 (20.0%) cases and 4 (5.3%) controls. XMRV and HCMV infections were detected in one and six control samples, respectively. The risk of PC was significantly increased (Odds Ratio = 3.98; 95% CI: 1.17-13.56, p = 0.027) by infection of the prostatic tissue with HPV. BKV, JCV, and SV40 sequences were not detected in any of the tissue samples examined. Conclusions: We report a positive association between PC and HPV infection. The 462Q/Q RNASEL genotype was not represented in our PC cases; thus, its interaction with prostate viral infections and cancer could not be evaluated.